Regional Economic Structure, Amenities and Disparities in an Extended Uzawa’s Growth Model - Wei-Bin Zhang (Eastern European Journal of Regional Studies, 2018)
The purpose of this paper is to extend Uzawa’s two-sector for a national economy to an economy with any number of regions. The paper studies interregional economic development with interactions among wealth accumulation, environmental change and economic structure under assumptions of profit maximization, utility maximization, and perfect competition. Although the model itself is a straightforward extension of Zhang’s two-region growth to any number of regions, the main contribution of this paper is that it succeeds in simulating the motion of the multi-region economy. This also enables us to effectively deal with comparative dynamic analysis to see how changes in local amenity, the propensity to save, the propensity to consume housing, and regional technologies have effects on national income and wealth, population distribution, regional environment within a general equilibrium theoretical framework.